Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.628
|View full text |Cite
|
Sign up to set email alerts
|

Sentence Meta-Embeddings for Unsupervised Semantic Textual Similarity

Abstract: We address the task of unsupervised Semantic Textual Similarity (STS) by ensembling diverse pre-trained sentence encoders into sentence meta-embeddings. We apply, extend and evaluate different meta-embedding methods from the word embedding literature at the sentence level, including dimensionality reduction (Yin and Schütze, 2016), generalized Canonical Correlation Analysis (Rastogi et al., 2015) and cross-view auto-encoders (Bollegala and Bao, 2018). Our sentence metaembeddings set a new unsupervised State of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Second, we expect that word prisms can improve performance in other tasks such as automatic summarization, which often use a single set of word embeddings in their input layers (Dong et al, 2019). Third, we believe that meta-embeddings and the method behind word prisms can be generalized past word-based representations to sentence representations (Pagliardini et al, 2018) and may improve their quality, as was recently demonstrated by Poerner et al (2019). Lastly, recent work has found simple word embeddings to be useful for solving diverse problems from the medical domain (Zhang et al, 2019), to materials science (Tshitoyan et al, 2019), to law (Chalkidis and Kampas, 2019); we expect that word prisms and their motivations can further improve results in these applications.…”
Section: Discussionmentioning
confidence: 84%
“…Second, we expect that word prisms can improve performance in other tasks such as automatic summarization, which often use a single set of word embeddings in their input layers (Dong et al, 2019). Third, we believe that meta-embeddings and the method behind word prisms can be generalized past word-based representations to sentence representations (Pagliardini et al, 2018) and may improve their quality, as was recently demonstrated by Poerner et al (2019). Lastly, recent work has found simple word embeddings to be useful for solving diverse problems from the medical domain (Zhang et al, 2019), to materials science (Tshitoyan et al, 2019), to law (Chalkidis and Kampas, 2019); we expect that word prisms and their motivations can further improve results in these applications.…”
Section: Discussionmentioning
confidence: 84%
“…There are many unsupervised approaches to obtaining sentence embeddings, for example by averaging word embeddings (Mikolov et al, 2013;Pennington et al, 2014;Bojanowski et al, 2017) or with carefully designed sentence-level objectives (Le and Mikolov, 2014;Kiros et al, 2015). Ensembling several methods improves results (Pörner and Schütze, 2019;Pörner et al, 2020). Recent work obtains sentence representations by supplementing BERT (Devlin et al, 2019) or other PLMs with additional unsupervised objectives (Zhang et al, 2020;Wu et al, 2020;Giorgi et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…For the combination, some alternatives have been proposed, such as different input channels of a convolutional neural network (Kim, 2014;Zhang et al, 2016), concatenation followed by dimensionality reduction (Yin and Schütze, 2016) or averaging of embeddings (Coates and Bollegala, 2018), e.g., for combining embeddings from multiple languages (Lange et al, 2020b;Reid et al, 2020). More recently, auto-encoders (Bollegala and Bao, 2018;Wu et al, 2020), ensembles of sentence encoders (Poerner et al, 2020) and attentionbased methods (Kiela et al, 2018;Lange et al, 2019a) have been introduced. The latter allows a dynamic (input-based) combination of multiple embeddings.…”
Section: Related Workmentioning
confidence: 99%